2009
DOI: 10.1177/0003319708330525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pravastatin on Serum Osteoprotegerin Levels in Patients With Hypercholesterolemia and Type 2 Diabetes

Abstract: Osteoprotegerin is a secretory glycoprotein. Recent experimental findings have suggested that osteoprotegerin may protect against vascular calcification and/or atherosclerosis. In humans, osteoprotegerin levels are positively correlated with the presence and severity of coronary artery disease and the progression of atherosclerosis. However, it is unclear how osteoprotegerin levels are regulated. Statins are known to have beneficial pleiotropic effects against atherosclerosis beyond their lipid-lowering effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Moreover, ibandronate and statins have been shown to inhibit RANKL expression and decrease OPG expression in human and mouse bone marrow stromal cells (Fernández et al, 2010;Kaji et al, 2005). Bisphosphonates and statins increased serum OPG concentration and decreased RANKL expression in osteoporosis and type 2 diabetes patients (D'Amelio et al, 2010;Dobnig et al, 2006;Mori et al, 2010;Nezami et al, 2010). Thus, bisphosphonates and statins may decrease RANKL expression and increase OPG expression and the OPG/RANKL ratio in bone marrow stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ibandronate and statins have been shown to inhibit RANKL expression and decrease OPG expression in human and mouse bone marrow stromal cells (Fernández et al, 2010;Kaji et al, 2005). Bisphosphonates and statins increased serum OPG concentration and decreased RANKL expression in osteoporosis and type 2 diabetes patients (D'Amelio et al, 2010;Dobnig et al, 2006;Mori et al, 2010;Nezami et al, 2010). Thus, bisphosphonates and statins may decrease RANKL expression and increase OPG expression and the OPG/RANKL ratio in bone marrow stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existing studies have been performed on different cohorts, including patients with diabetes type 2 only or CAD only, as well as patients with both diabetes type 2 and microalbuminuria or hypercholesterolemia [5356]. Among them, 3 studies documented serum OPG elevation during statins therapy (lovastatin or simvastatin therapy) [53,54,56], whereas another study reported OPG reduction during pravastatin therapy [55]. Serum RANKL levels were only assessed in 1 of the above studies, being reduced during lovastatin therapy [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, atorvastatin treatment in patients with carotid stenosis reduced serum OPG levels [79]. On the contrary, Mori et al [80] showed that OPG levels were slightly increased (6.6%) after 3-month treatment with pravastatin in patients with hypercholesterolemia and type 2 diabetes, regardless of cholesterol levels, thus suggesting that pravastatin may exert its pleiotropic effects in part through alteration of OPG levels. One possible explanation for this discrepancy is the use of different statins, as pravastatin treatment increased adiponectin levels, which have beneficial effects on insulin resistance and atherosclerosis both in vitro and in vivo [81] and in humans [82,83] while simvastatin treatment failed to affect adiponectin levels and insulin sensitivity [84].…”
Section: Opg and Obesity Lipid Profile And Metabolic Syndrome In Diamentioning
confidence: 96%